Diversity of Individual Dynamic Patterns of Emergence of Resistance to Quinolones in Escherichia coli From the Fecal Flora of Healthy Volunteers Exposed to Ciprofloxacin - de Lastours, Victoire; Cambau, Emmanuelle; Guillard, Thomas; Marcade, Géraldine; Chau, Françoise; Fantin, Bruno (The Journal of infectious diseases, 2012)
Background. Emergence of quinolone-resistant Escherichia coli (QREC) is an increasing clinical challenge mostly originating in fecal microbiota. The dynamics of the emergence of QREC in feces from individuals exposed to ciprofloxacin is unknown. Methods. A total of 48 healthy volunteers received oral ciprofloxacin for 14 days. Fecal specimens were collected on days 0, 8, 14, and 42. Subpopulations of QREC were detected on selective agar, genetically characterized, and compared with quinolone-susceptible E. coli (QSEC) strains collected on different days. Results. On day 42, 34 subjects carried QSEC, and 14 carried QREC. Of the 14 who carried QREC, 9 carried quinolone-susceptible E. coli on day 0, 1 carried E. coli with a lower level of quinolone resistance on day 0, and 4 carried E. coli with similar levels of resistance and RAPD-genotypes on days 0 and 42. No plasmid acquisition and no selection of resistant mutants from the initial microbiota was evidenced in any case. Conclusions. In QREC emerging under ciprofloxacin pressure in the fecal microbiota, no proof of selection of quinolone-resistant mutants from the initial microbiota was evidenced, suggesting that QREC strains on day 42 were either present at undetectable levels in the initial microbiota or that exogenous acquisition of QREC strains occurred.